Estimate of the financial value of timber stocks of red cedar (Cedrela odorata L.) in Mexico - Romo-Lozano, José Luis; Vargas-Hernández, Jesús; López-Upton, Javier; Avila Angulo, María Luisa (Instituto de Ecología, A.C., 2017)
One of the two large categories of economic valuation within the environmental services field associated to natural resources is the market valuation. As its name implies, this type of valuation uses information generated in the process of exchange of goods or services valued. This document contains a financial valuation effort of Spanish red cedar (Cedrela odorata L.) species in Mexico. In this exercise the market price method was applied in order to estimate the monetary value of its main use (timber), considering the standing wood volume of the species in natural forests, based on information generated from the national forest inventory database. The effect of wood volume, price and transportation cost on total value was evaluated through a sensitivity analysis. The estimated value for total standing timber was MXN$ 5 282 183 404 (USD$288 328 788 at May 2016 prices). The Gulf of Mexico region has the highest value representation among the three regions considered in this paper. According to the sensitivity analysis, the price of wood is the main factor affecting total timber value of the species.